National Firearms Survey, 1999 - Hemenway, David ([Verlag nicht ermittelbar], 2007)
This survey was undertaken to obtain information on the characteristics of gun ownership, gun storage and gun carrying practices, and weapons-related incidents in the United States--specifically, use of guns and other weapons in self-defense against other people. Data were collected using national random-digit dial telephone surveys completed between March 19, 1999 and July 13, 1999. Sampling was suspended after the school shooting in Littleton, Colorado on April 20, 1999, and resumed after a cool-down period. Part 1, Survey Data, contains the coded data obtained during the interviews, and Part 2, Open-Ended Verbatim Responses, consists of open-ended answers provided by the respondents. Four qualifying questions were asked, dealing with: (1) gun ownership, (2) gun display against the respondent, (3) gun use in self-defense against another person, and (4) the use of a weapon other than a gun in self-defense against another person. A "yes" response to a qualifying question led to a series of additional questions on the same topic as the qualifying question. Information was collected from all respondents on the perceived safety of their neighborhood, whether they would feel safer if more people owned guns, whether guns should be allowed in public places, whether gun injuries were a problem in their community, whether they would favor or oppose a program to reduce gun injuries, and whether they had ever been shot with a gun. Respondents living in households that currently contained a gun were asked how many and what type of guns were present, the main reasons for owning a gun, whether any of the guns were loaded and unlocked, and whether they had received formal firearms training. Questions about incidents in which a gun was displayed in a hostile manner against the respondent included the number of times it took place, how long ago it had occurred, whether the respondent was in the military or police force at the time, the location of the incident, whether the individual displaying the gun was known to the respondent, whether the respondent had a gun, and whether the police were contacted. Respondents who had used a gun or other weapon in self-defense in the last five years were asked about the number of times it took place, the location of the incident, whether they were in the military or police force at the time, the type of weapon used, whether they knew the other person, whether this individual also had a weapon, whether the police were contacted and arrests made, and what crime was committed. Additional questions asked respondents whether they smoked cigarettes, drank alcohol, whether they had gotten married, had had a fire in their home, and had been hospitalized for a fracture in the past year, and whether they had ever had contact with extraterrestrial life. Demographic variables include sex, age, race, education level, household income, type of residential area (e.g., urban, rural, etc.), and age and number of children in the household.